Upaya Preventif terhadap Aksi Vandalisme di Kabupaten Karawang oleh Satpol PP - Raden Nisfa Syabana; Lina Aryani; Evi Priyanti (Fakultas Teknik Universitas Cenderawasih, 2026)
Vandalism is a social problem affecting public space quality, urban aesthetics, and the effectiveness of public facilities utilization. Karawang Regency, as a developing industrial area, faces challenges related to increasing acts of vandalism targeting public facilities, open spaces, and government and private assets. This study aims to analyze preventive efforts carried out by the Civil Service Police Unit (Satpol PP) of Karawang Regency using J. Salusu’s public sector strategic management perspective. This research employed a qualitative approach with a descriptive case study method. Data were collected through observation, interviews, and documentation involving Satpol PP officers and public facility users. Data analysis consisted of data reduction, data display, and conclusion drawing with source, technique, and time triangulation. The findings indicate that preventive strategies have been implemented through four strategic management phases. In the identification phase, Satpol PP recognized vandalism patterns but lacked systematic mapping of vulnerable locations. In the development phase, institutional strengths existed alongside limitations in resources and innovation. In the resolution phase, strategies focused on socialization, routine patrols, and cross-sector collaboration. In implementation and evaluation, preventive programs operated adaptively but still encountered limitations in personnel capacity and public participation. Strengthening technology utilization, human resources, and collaborative governance is necessary to improve long-term preventive effectiveness.